2020
DOI: 10.1007/s40259-019-00402-0
|View full text |Cite
|
Sign up to set email alerts
|

Batch-to-Batch Consistency of SB4 and SB2, Etanercept and Infliximab Biosimilars

Abstract: Background Biosimilars must meet stringent regulatory requirements, both at the time of authorization and during their lifecycle. Yet it has been suggested that divergence in quality attributes over time may lead to clinically meaningful differences between two versions of a biologic. Therefore, this study investigated the batch-to-batch consistency across a range of parameters for released batches of the etanercept biosimilar (SB4) and infliximab biosimilar (SB2). Methods SB4 (Benepali ® ) and SB2 (Flixabi ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Our observations reveal that minor differences in certain QAs between biosimilars and reference biological can occur at the same level of variability between pre-and postmanufacturing change batches of the reference biological [23,35,63], which reassures the biosimilar regulation system. Although EU regulators have focused on describing pCQAs, these critical attributes were not explicitly defined in EPARs.…”
Section: Discussionmentioning
confidence: 57%
“…Our observations reveal that minor differences in certain QAs between biosimilars and reference biological can occur at the same level of variability between pre-and postmanufacturing change batches of the reference biological [23,35,63], which reassures the biosimilar regulation system. Although EU regulators have focused on describing pCQAs, these critical attributes were not explicitly defined in EPARs.…”
Section: Discussionmentioning
confidence: 57%
“…Five of the identified references reported analytical studies with SB2 [9][10][11][12][13] (eAppendix 2).…”
Section: Search Resultsmentioning
confidence: 99%
“…An analysis of 25 different batches of SB2 demonstrated that the purity, protein concentration, TNF-α binding, and TNF-α neutralization capabilities of all batches were within the strict specification limits set by regulatory agencies, demonstrating batch-to-batch consistency [10]. The batch-to-batch consistency of SB2 is further supported by a study analyzing three lots of SB2, reconstituted as per EU Summary of Product Characteristics (SmPC) [36], diluted or undiluted and stored under different conditions (4°C and 25°C) [12].…”
Section: Physicochemical and Biological Characterization Of Sb2mentioning
confidence: 89%
See 1 more Smart Citation
“…At the same time, the authors caution that persistent antibodies to infliximab may be detected at least 1 year after therapy discontinuation, and drug batches could be subtly different (more or less immunogenic). However, considering manufacturers of biosimilars are compelled to vigilantly abide by rigorous quality standards in accordance with regulatory approval specifications, batch-to-batch drifting of the quality attributes of biosimilars is routinely precluded to any extent that is clinically meaningful [ 130 ]. For that reason, the proposed drug batch-to-batch–related limitation suggested in relation to the Fiorina et al, study seems improbable.…”
Section: Evidence Of the Safety And Efficacy Of Biosimilar Cross-switchingmentioning
confidence: 99%